Liderazgo y desempeño laboral en la Cooperativa de Ahorro y Crédito Kullki Wasi, Matriz Ambato. - Ortega Calala, Pamela Maribel (2024)
The objective of this research was to analyze the relationship between leadership and work performance in the head office of the Kullki Wasi Savings and Credit Cooperative in Ambato. A methodology that combined qualitative and quantitative approaches was employed, using a literature review, observation, interviews, surveys, and a questionnaire based on contributions from Arias & Muñoz (2021) and Geraldo (2022), based on a Likert scale from 1 to 5. The sample consisted of 80 employees. The findings showed significant deficiencies in several aspects. An 18.8% deficiency in health and well-being was observed, while 25% of the participants indicated the absence of motivational training programs. In addition, there was low participation in organizational activities, reaching 21.3%. In terms of leadership, a 15% lack of work-life balance policies was detected, along with a 17.5% need to evaluate leadership practices. Statistical analyses supported these findings, with a normality test yielding a significance of p=0 and a Spearman correlation of 0.805. Strategies aimed at addressing these deficiencies were proposed, such as workshops and training on stress management and relaxation techniques, a points-based reward system, incorporation of technological tools, shift sharing, and leadership style assessment.